Psychological Services in Immoral Cases: Psychological Recovery Efforts Through a Trauma-Focused Cognitive Behavior Therapy Approach - Kusumastuti, Wanodya; Kusuma, Patria Jati (Maslahah: Jurnal Pengabdian Masyarakat, 2026)
This service activity aims to provide psychological recovery services based on Trauma-Focused Cognitive Behavioral Therapy (TF-CBT) that is structured and integrated with spiritual education, as well as strengthening the service capacity of the Integrated Service Center for the Protection of Women and Children (PPA) of Purworejo Regency. The method used is a participatory-collaborative approach based on community-based intervention, including initial psychological assessment, the implementation of individual counseling at least three sessions per client, and monitoring and evaluation of pre- and post-intervention conditions. Participants consisted of adolescent girls and adult women who were victims of sexual violence referred by the PPA. The results of the activity showed a decrease in the intensity of anxiety, emotional distress, and trauma symptoms, accompanied by an increase in the ability to regulate emotions, adaptive coping, and the recovery of self-concept and hope for the future. The program also produces spiritually integrated TF-CBT intervention modules and educational materials for partners. Thus, TF-CBT is effective as a contextual and sustainable community-based model of psychological recovery. Keywords: Trauma-Focused Cognitive Behavioral Therapy (TF-CBT), Sexual Violence, Psychological Recovery.